Evaluating the Lifetime Performance Index Based on the Bayesian Estimation for the Rayleigh Lifetime Products with the Upper Record Values - Wen-Chuan Lee; Jong-Wuu Wu; Ching-Wen Hong; Shie-Fan Hong (Journal of Applied Mathematics)
Quality management is very important for many manufacturing industries. Process capability analysis has been widely applied in the field of quality control to monitor the performance of industrial processes. Hence, the lifetime performance index CL is utilized to measure the performance of product, where L is the lower specification limit. This study constructs a Bayesian estimator of CL under a Rayleigh distribution with the upper record values. The Bayesian estimations are based on squared-error loss function, linear exponential loss function, and general entropy loss function, respectively. Further, the Bayesian estimators of CL are utilized to construct the testing procedure for CL based on a credible interval in the condition of known L. The proposed testing procedure not only can handle nonnormal lifetime data, but also can handle the upper record values. Moreover, the managers can employ the testing procedure to determine whether the lifetime performance of the Rayleigh products adheres to the required level. The hypothesis testing procedure is a quality performance assessment system in enterprise resource planning (ERP).